1999
DOI: 10.1046/j.1523-5378.1999.99291.x
|View full text |Cite
|
Sign up to set email alerts
|

Colonization and Tissue Tropism of Helicobacter pylori and a Novel Urease‐Negative Helicobacter Species in ICR Mice Are Independent of Route of Exposure

Abstract: The isolation of H. pylori and the novel Helicobacter sp. from multiple tissues infers that a transient helicobacter bacteremia occurs when Helicobacter spp. are injected intraperitoneally, but organisms are cleared rapidly from nontarget tissues and preferentially colonize specific regions of the gastrointestinal tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Similarly, serum IgG levels were high in Swiss Webster outbred mice dosed intraperitoneally with H. pylori, even though only a minority (one out of eight) of the mice was colonized with H. pylori 1 month after dosing. The serum titres were considerably greater than antibody titres measured in orally dosed mice (McCathey et al, 1999). In mice dosed intraperitoneally with an enteric helicobacter, the organism was not isolated from various tissues (blood, lung, spleen, liver and kidneys) 30 days p.i., but was cultured from faeces (McCathey et al, 1999).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Similarly, serum IgG levels were high in Swiss Webster outbred mice dosed intraperitoneally with H. pylori, even though only a minority (one out of eight) of the mice was colonized with H. pylori 1 month after dosing. The serum titres were considerably greater than antibody titres measured in orally dosed mice (McCathey et al, 1999). In mice dosed intraperitoneally with an enteric helicobacter, the organism was not isolated from various tissues (blood, lung, spleen, liver and kidneys) 30 days p.i., but was cultured from faeces (McCathey et al, 1999).…”
Section: Discussionmentioning
confidence: 73%
“…The bacterial pellet was resuspended in sterile PBS to a concentration of approximately 10 7 organisms ml 21 based on spectrophotometric examination. Using a previously published inoculation strategy, experimental mice (24 males, 24 females) received 0.2 ml inoculum by intraperitoneal injection, whilst control mice (8 males, 8 females) were given 0.2 ml sterile PBS (McCathey et al, 1999;Shomer et al, 2001). One mouse from each cage (total of two control and six experimental mice of each sex) was necropsied at 6 and 12 months after dosing; necropsies on the remaining mice were performed when the study was concluded at 18 months postinoculation (p.i.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that mice inoculated intraperitoneally with H. pylori develop acute hepatitis [21]. We established the mouse model of H. pylori infection by inoculating orally instead of intraperitoneally, as the usual route of H. pylori infection is faecal-oral.…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed this by the presence of chronic inflammation in the livers of ip-treated mothers but not ig-treated mothers. In a study with H. pylori and a novel Helicobacter species, McCathey et al (1999) found that ip-administered bacteria, but not ig administration at the same titer, resulted in hepatitis and elicited a much greater immune response. Thus, the likelihood of transmission of progressive disease to offspring may be a function of degree of infection of the mother, and the very high incidences of hepatitis and tumors in male offspring of naturally infected mothers, seen in our original population of infected mice, may reflect the level of bacterial burden accumulated over generations.…”
Section: Discussionmentioning
confidence: 99%